공기측 입구헤더의 형상 개선을 통한고분자 전해질 연료전지의 성능 향상 - 김원년; 김윤호; 김서영 (대한설비공학회, 2007)
In the present study, a 10-cell PEMFC stack with straight type cathode flow channels is employed to investigate the effect of inlet air flow header configuration on the overall fuel cell performance. Four different types of inlet flow headers are considered and the flow patterns according to the air inlet flow header configuration are numerically obtained. The computed result for a modified header predicts about 8.5% improvement in the air flow distribution at 10-cell cathode channel inlets. Experiments are also carried out to confirm the numerical findings by measuring actual air flow distributions and the polarization curves of the PEMFC stack.